PELAKSANAAN TUGAS DAN TANGGUNGJAWAB ROOM ATTENDANT DI TJOKRO HOTEL PEKANBARU - Pasaribu, Wira Wida; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Hotel is one type of accommodation that uses part or all of the building to provide lodging, eating and drinking services and other services that are managed commercially. A hotel certainly has a department that has a big role, one of which is the Housekeeping Department. Housekeeping Department is part of the hotel department that is responsible for the cleanliness, tidiness and comfort of guest rooms, public areas, restaurants, bars and other outletsThe purpose of this study was to find out how to work and what were the obstacles to the implementation of the duties of the room attendant Housekeeping department at the Tjokro Hotel Pekanbaru. In writing this paper, the author uses qualitative data analysis techniques, namely analyzing, describing and summarizing various conditions, situations from various data collected in the form of results from interviews and observations about the problems studied that occur in the field. Keywords: Hotel, Housekeeping department, Room attendant.